Effect of discontinuous glass fibers on mechanical properties of glass ionomer cement. Issue 1 (1st January 2018) - Garoushi, Sufyan K.; He, Jingwei; Vallittu, Pekka K.; Lassila, Lippo V. J.
Abstract: Aim: This study investigated the reinforcing effect of discontinuous glass microfibers with various loading fractions on selected mechanical properties of self-cure glass ionomer cement (GIC). Method: Experimental fiber reinforced GIC (Exp-GIC) was prepared by adding discontinuous glass microfiber (silane/non-silane treated) of 200–300 µm in length to the powder of self-cure GIC (GC Fuji IX) with various mass ratios (15, 20, 25, 35, and 45 mass%) using a high speed mixing device. Flexural strength, flexural modulus, work of fracture, compressive strength and diametral tensile strength were determined for each experimental and control materials. The specimens ( n  = 8) were wet stored (37 °C for one day) before testing. Scanning electron microscopy equipped with energy dispersive spectrometer was used to analysis the surface of silanized or non-silanized fibers after treated with cement liquid. The results were analyzed with using multivariate analysis of variance MANOVA. Results: Fiber-reinforced GIC (25 mass%) had significantly higher mechanical performance of flexural modulus (3.8 GPa), flexural strength (48 MPa), and diametral tensile strength (18 MPa) ( p  < .05) compared to unreinforced material (0.9 GPa, 26 MPa and 8 MPa). No statistical significant difference in tested mechanical properties was recorded between silanized and non-silanized Exp-GIC groups. Compressive strength did not show any significant differences ( p  > .05) between the fiber-reinforced and unreinforced GIC. Conclusion: The use of discontinuous glass microfibers with self-cure GIC matrix considerably increased the all of the studied properties except compressive strength.